Interior Architecture Sustainability in Heritage Buildings in Historical Jeddah; a Natural Lighting Pattern Analysis - Waheeb, Sahl (Journal of King Abdulaziz University: Environmental Design Sciences, 2023)
The research investigates the sustainable aspects through the analysis of natural lighting and the interior spaces of the historical Hijazi buildings in Jeddah. This scope of the study lies in the vision of the Kingdom of Saudi Arabia 2030 about preserving heritage and sustainability in construction, and conservation. The research reviews the patterns of natural lighting and cross ventilation and evaluates how they are in harmony with the concepts of sustainability in the rehabilitation of internal spaces that are integrated with it. Three natural lighting patterns were identified for the study. The case study of study involved Al-Kharja, the Roshan, and the Qamaria. The patterns were selected based on the size where Al-Kharja was considered the large source of natural lighting; Roshan was a medium and Qamaria was a small source of natural lighting in old Jeddah houses. Furthermore, the study highlights the crucial role of the cross-ventilation system in effectively regulating the outflow cycle of hot air and promoting cool breezes within houses and buildings. Notably, natural lighting emerges as a fundamental aspect of interior space sustainability, profoundly influenced by space utilization and ongoing rehabilitation endeavors. The findings provide valuable insights for researchers, architects, and governmental entities, guiding the design of sustainable building codes and advocating the adoption of lightweight yet sustainable materials in modern construction practices.